P54. Differences in neuronal representation of mental rotation in CRPS patients and healthy controls. Issue 8 (August 2018) - Kohler, M.; Strauß, S.; Horn, U.; Usichenko, T.; Langner, I.; Domin, M.; Lotze, M.
Abstract : Spatial integration of the body matrix, especially representation of the affected side is reduced in patients suffering from complex regional pain syndrome (CRPS;Moseley et al., 2009 ). The parietal sulcus integrates multimodal sensory input to spatial aspects of the own body and is therefore essential for processing mental rotation (MR) (Lebon et al., 2012). Since the training of MR has turned out to be among the effective therapy strategies for CRPS (Graded motor imagery; GMI; Moseley et al., 2006), MR is also important for the pathophysiological understanding of CRPS. The aim of this study was to point out differences in neural representation of MR in a group of CRPS patients and healthy controls. Therefore we included 15 CRPS patients (DASH-Avg.: 51.54; CSS: 12.39; pain intensity 4.36 of 10 VAS; age: 58 years; CRPS duration 21 ± 20 months) and 15 age-/gender matched healthy controls. We assessed behavioral (reaction time in MR for both hands), clinical (CRPS-severity, somatosensory and motor function) and MRI (T1, fMRI during MR, connectivity during rest) data. Our data of reaction time in patient group showed a bilateral MR delay compared to healthy controls ( t (28) = 2.39; p = 0.02). There was no lateralization effect. As expected (Berneiser et al., 2017) for healthy controls fMRI demonstrated an active network from visual recognition (occipital cortex (OC)), parietal sulcus (PS), and primary motor cortex (M1). The same network was less expressed in activation magnitude in CRPS patients (pFWE corrected for ROI-analysis). Correlation analysis between clinical aspects, MRI data and connectivity measures (DCM: OCG-PS-M1) are still being evaluated.